Culture shapes nursing practice: Findings from a New Zealand study. Issue 11 (November 2017) - Crawford, Ruth; Stein-Parbury, Jane; Dignam, Denise
Highlights: Parents of a child in hospital are isolated and feel vulnerable. Nurses are unprepared to manage parent's emotions. Parents want nurses to be the cultural broker between the parent and the hospital unit. The context and culture of a hospital unit influences nurse-parent communication. Abstract: Objectives: This paper reports research undertaken to investigate nurses' and parents' experiences of communication about parental emotions in a hospital setting, with a focus on the environmental and cultural context within which the communication occurs. Methods: A focused ethnography was employed as the aims were to understand the context within which nurse-parent interaction takes place, by exploring cultural factors, such as ways of living affecting nursing communication. Data collection occurred in a children's unit of a New Zealand hospital, involving 260 h of participant observation field work, informal interviews with parents and nurses, followed by 20 formal interviews with nurses and parents. Results: Nurses are cultural brokers, with the potential to be a link between the insider culture, the hospital and the outside, the parents. Parents look to nurses for cultural brokerage, to help them cross the strong cultural boundaries present in a hospital unit. Conclusion: The context and culture of a hospital unit influences nurse-parent communication. There is a disconnection between parents' emotional needs in hospital and nurses' ability to meet those needs. Practice implications: Nurses must be supported to provide effective cultural brokerage for parents. Unit managers need to acknowledge that meeting parents' diverse needs is vital.